Small Farm Food Safety, Fresh Produce: Instructions for Trainer - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS, 2007)
FCS8841, a 2-page factsheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, introduces trainers to the "Small Farm Food Safety, Fresh Produce" curriculum, which is designed to help small-scale farmers correctly follow proper food safety practices. It gives a brief overview of the curriculum. Published by the UF Department of Family, Youth and Community Sciences, October 2007.